Defining a disproportionate burden in transboundary fisheries: Lessons from international law. (August 2016) - Azmi, Kamal; Davis, Ruth; Hanich, Quentin; Vrahnos, Adam
Abstract: The international legal framework for fisheries governance requires that conservation and management measures for transboundary fish stocks do not place a disproportionate burden on developing States. Yet this framework does not define "disproportionate" nor does it make clear the criteria against which the balance of a conservation burden might be judged to be disproportionate. This gap in the legal framework exacerbates conflicts over transboundary fisheries resources, and undermines the ability of small island developing states, such as those in the Western and Central Pacific, to enjoy fully the benefits of the resources in their exclusive economic zones. It also constrains the ability of regional fisheries management organisations (RFMOs) to ensure the long term sustainability of stocks. This paper considers how the question of proportionality has been addressed in other areas of international law, including use of force, maritime boundary delimitation, climate change, international watercourses and trade. It finds that while approaches to proportionality are influenced by the context of the regime in which it is applied, they can nevertheless provide useful lessons for RFMOs and their Members in designing equitable conservation and management measures that do not place a disproportionate conservation burden on developing countries.